2021
DOI: 10.3390/nano11102720
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gold Nanorods Conjugated with Synthetic Glycopolymers Using an Analytical Approach Based on spICP-SFMS and EAF4-MALS

Abstract: A new comprehensive analytical approach based on single-particle inductively coupled plasma-sector field mass spectrometry (spICP-SFMS) and electrical asymmetric-flow field-flow-fractionation combined with multi-angle light scattering detection (EAF4-MALS) has been examined for the characterization of galactosamine-terminated poly(N-hydroxyethyl acrylamide)-coated gold nanorods (GNRs) in two different degrees of polymerization (DP) by tuning the feed ratio (short: DP 35; long: DP 60). spICP-SFMS provided infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…UV–vis spectroscopy revealed a red shift of the longitudinal LSPR band for the glyco-coated GNRs, ζ-potential indicated a decrease of negative surface charge, and TEM showed that the nanorod dimensions were retained during coating, while DCS and NTA analyses indicated an increase in particle size compared with the citrate-GNRs, as expected (see Table ). When nanoparticles are coated and therefore the resulting density and size are changed, their size measured by DCS is altered, showing here a shift toward apparent smaller diameters. , Altogether, these data confirmed the successful attachment of the glyco ligands to the particle surface and their stability in a colloidal suspension.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…UV–vis spectroscopy revealed a red shift of the longitudinal LSPR band for the glyco-coated GNRs, ζ-potential indicated a decrease of negative surface charge, and TEM showed that the nanorod dimensions were retained during coating, while DCS and NTA analyses indicated an increase in particle size compared with the citrate-GNRs, as expected (see Table ). When nanoparticles are coated and therefore the resulting density and size are changed, their size measured by DCS is altered, showing here a shift toward apparent smaller diameters. , Altogether, these data confirmed the successful attachment of the glyco ligands to the particle surface and their stability in a colloidal suspension.…”
Section: Resultssupporting
confidence: 75%
“…When nanoparticles are coated and therefore the resulting density and size are changed, their size measured by DCS is altered, showing here a shift toward apparent smaller diameters. 40,41 Altogether, these data confirmed the successful attachment of the glyco ligands to the particle surface and their stability in a colloidal suspension.…”
Section: Gold Nanorods Functionalization and Stabilitysupporting
confidence: 67%
“…EAF4 is still in its infancy and the scarce studies carried out so far to optimize the carrier for the determination of µ and/or ζ are limited to exosomes, liposomes, proteins, and polystyrene latex particles [15,17,18]. Other authors have used EAF4 for Au nanorods recently, but only to confirm that those NPs carry negative charge and thereby confirming the ζ obtained by a separate instrument [19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, four main categories can be distinguished based on their nature [ 1 ]: (1) carbon-based nanomaterials, which are found in morphologies such as ellipsoids or spheres, hollow tubes, or ultrathin sheets; fullerenes (C 60 ), carbon nanotubes (CNTs), carbon nanofibers, carbon black, graphene (G), and its derivatives graphene oxide (GO) and reduced graphene oxide (rGO) are in this category [ 2 , 3 ]. (2) Inorganic-based nanomaterials, which include metal [ 4 ] and metal oxide nanoparticles, such as TiO 2 , SnO and ZnO [ 5 , 6 , 7 ], and semiconductors, such as silicon, III-V compounds, transition metal dichalcogenides, Xenes, etc. [ 8 ].…”
mentioning
confidence: 99%
“…The articles present very different types of nanomaterials, such as gold nanorods [ 4 ], WTe 2 nanocrystals [ 11 ], CaCO 3 nanoparticles [ 12 ], ferromagnetic nanoparticles [ 13 ], CuO nanocrystals and single-walled carbon nanotubes [ 14 ], graphene [ 3 ], and GO derivatives [ 15 ].…”
mentioning
confidence: 99%